Perancang Sistem Informasi Buku Tamu Berbasis Web untuk Meningkatkan Efesiensi Pelayanan di Dinas PUPR Kota Jambi - M. Taufik Isti Nugraha; Gibran Lazmi; Al Muzakir; Desy Ika Haryani; One Azizah (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The Department of Public Works and Spatial Planning (PUPR) of Jambi City is a government institution that provides various public services, including visitor administration services. The manual guest registration process causes several problems such as difficulties in data retrieval, risk of data loss, and inefficient visitor information management. This study aims to design a web-based guest book information system to improve service efficiency at the PUPR Office of Jambi City. The research applied the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The system was developed using PHP programming language and MySQL database. The results indicate that the web-based guest book information system facilitates visitor registration, accelerates data retrieval, supports visitor report management, and improves administrative service efficiency. The implementation of this system makes visitor data management more organized, effective, and accessible.